A Light‐Activatable Photocaged Variant of the Ultra‐High Affinity ALFA‐Tag Nanobody. (27th April 2022) - Jedlitzke, Benedikt; Mootz, Henning D.
Abstract: Nanobodies against short linear peptide‐epitopes are widely used to detect and bind proteins of interest (POI) in fusion constructs. Engineered nanobodies that can be controlled by light have found very recent attention for various extra‐ and intracellular applications. We here report the design of a photocaged variant of the ultra‐high affinity ALFA‐tag nanobody, also termed ALFA‐tag photobody. ortho ‐Nitrobenzyl tyrosine was incorporated into the paratope region of the nanobody by genetic code expansion technology and resulted in a ≥9, 200 to 100, 000‐fold impairment of the binding affinity. Irradiation with light (365 nm) leads to decaging and reconstitutes the native nanobody. We show the light‐dependent binding of the ALFA‐tag photobody to HeLa cells presenting the ALFA‐tag. The generation of the first photobody directed against a short peptide epitope underlines the generality of our photobody design concept. We envision that this photobody will be useful for the spatiotemporal control of proteins in many applications using cultured cells. Abstract : Tag control : Photo‐activatable antibodies are a recent addition to the chemical biology toolbox that allow the manipulation of biological processes by antigen‐binding with unprecedented spatiotemporal control. We report the successful extension of our design concept of suitably photocaged nanobodies, termed photobodies, to the first short tag (13 amino acids) binding nanobody, the ultra‐high affinity ALFA nanobody, to open the door for more fine‐tuned control.